Effect of Prior Cheilectomy on Outcomes of First Metatarsophalangeal Joint Fusion for Treatment of Hallux Rigidus. Issue 3 (August 2022) - Rajan, Lavan; Kim, Jaeyoung; An, Tonya; Mizher, Rami; Srikumar, Syian; Fuller, Robert; Zhu, Jiaqi; Ellis, Scott J.
Background: Patients with hallux rigidus who do not experience significant pain relief after cheilectomy often require a conversion to metatarsophalangeal (MTP) fusion. However, it is unclear whether the previous cheilectomy affects outcomes of the subsequent fusion. The aim of this study was to compare patient-reported outcomes and complications in patients undergoing MTP fusion for hallux rigidus between patients with a history of cheilectomy and those undergoing a fusion as a primary procedure. Methods: This retrospective cohort study included patients who underwent MTP fusion who had preoperative and minimum 1-year postoperative Patient Reported Outcomes Measurement Information System (PROMIS) scores. Patients were divided into a "primary MTP fusion" cohort and a "prior cheilectomy" cohort based on their history of a previous cheilectomy. Preoperative, postoperative, and improvement in PROMIS scores, along with rates of complications including nonunion, infection, interphalangeal (IP) joint pain, and removal of hardware were compared between groups. Results: The prior cheilectomy group had significantly lower preoperative physical function scores than the primary MTP fusion group ( P < .05). Postoperatively, the prior cheilectomy group had worse physical function ( P < .017) and global physical health ( P < .017) scores. However, there were no significant differences in pre- to postoperative change in PROMIS scores. There were no significant differences in rates of nonunion ( P = .99), infection ( P = .99), or hardware removal ( P = .99). More patients in the prior cheilectomy group had IP joint pain ( P = .034). Conclusion: This study found that a prior cheilectomy may not affect serious complication rates of a subsequent fusion, but it may be associated with worse baseline function. Overall, our results suggest that a prior failed cheilectomy does not influence the amount of improvement in function and pain from MTP fusion. Level of Evidence: Level III, retrospective cohort study.